Penelitian penyusunan database tunggakan piutang pajak hotel di Kota Malang - Cindy Getah June (University of Merdeka Malang, 2022)
Tax arrears are the amount of tax payable that has not been paid by the Taxpayer. This tax arrears is caused by 2 (two) things, namely: due to the examination conducted by the tax collector. This inspection includes: Tax Assessment Letter (SKP). This Tax Assessment Letter (SKP) is issued limited to certain Taxpayers caused by incorrect filling in the Tax Return (SPT) or due to the discovery of physical data that is not reported by the Taxpayer.Tax Collection Letter (SPT) is a letter to collect taxes and or administrative sanctions in the form of interest and or fines for Taxpayers. If the billing field finds arrears due to the above, an active collection action will be taken as a means to collect taxes from the taxpayer. The total hotel tax arrears in Malang City are 103 taxpayers who have not paid and will be submitted for tax write-off.